Growth of young Tabebuia aurea seedlings under irrigation with wastewater from fish farming - Pinto,José R. de S. (2016)
ABSTRACT This study aimed to evaluate the growth of young Tabebuia aurea seedlings irrigated with different concentrations of wastewater from fish farming. The experiment was conducted in a seedling nursery, from June to August 2013. The treatments consisted of five concentrations of wastewater from fish farming diluted in freshwater (0, 25, 50, 75 and 100% of wastewater). Plant height, stem diameter and plant height/stem diameter ratio were evaluated every 15 days to verify the effects of treatments on seedlings growth. At the end of the experiment, individual leaf area, leaf area, leaf dry matter, stem dry matter, root dry matter, total dry matter and Dickson quality index were also evaluated. The reuse of wastewater from fish farming diluted at concentrations of 25 and 50% in freshwater is a viable alternative in the production of Tabebuia aurea seedlings. However, higher concentrations hinder the production of seedlings of this species.